Investigating the anti-acne potential of endophytic bacterial extracts isolated from Mangifera casturi in indigenous South Borneo, Indonesia - Sogandi, Sogandi; Riyanto, Julius (Future Science, 2020)
Endophytic bacteria are beneficial microorganisms living in the tis-sues system of various parts of a plant, including fruits, leaves, twigs, and roots. The bacteria are stated as forming colonies without caus-ing any damage to the plant. Thus, this study aimed at isolating endo-phytic bacterial from the leaves, barks, and fruits of Kasturi plant (Mangifera casturi), screening its endophytic bacteria, determining the potential of those endophytic bacteria, identifying 16S rRNA and analyzing potential growth of the bacteria. The isolated endophytic bacteria appeared to show potential activity against pathogenic bac-teria Propionibacterium acnes with disc-diffusion methods. Besides, the observations on bacterial activities showed isolate L2, S2 and F4 isolated from leaves, bark and fruits, respectively, as the most potent producers of antibacterial compounds. Technically, those activities were indicated by the formation of clear zones. Molecular identifica-tion was investigated by applying PCR amplification on 16S rRNA gene. Furthermore, the isolate L2 was identified as Enterobacter clo-acae with 99% sequence similarities; however, isolates S2 and F4 were identified as Escherichia coli. Therefore, these findings sug-gested that the identified strains would contribute to any further searches for new sources of anti-acne substances.